Teological Views of Imam Maturidi - Raizayeva, G.; Nurmatov, Zh. (Eurasian Journal of Religious Studies, 2022)
The article analyzes the theological system of Imam Abu Mansur al-Maturidi and his theologians, the founder of the Maturidiyya Madhhab, which is widespread in Central Asia as a sect of Islam. It is stated that Imam Maturidi developed his school following the tradition of Imam Aqzam Abu Hanifa, the main sect of the Ahl as-Sunnah wa’l-Jama’ah. Maturidi’s views focus on reason and provide a detailed description of his role in the knowledge of God. Here are the opinions of the students who continued the school of the scholar. We have also paid special attention to the theological significance and methods of the two books "Tawilatu-l Quran" and "Kitabu-t Tawhid", which have survived to the present day. Imam Maturidi’s works discuss the issues of "divinity", "human will and desire", "destiny", "prophethood", "faith and great sin". Also, Imam Maturidi’s theological views include "knowledge of God", "art and ugliness", "human freedom", "imposing an insurmountable task", "taqwa", "wisdom and reason", "hearing the word of God", "prophets". The issue of being a man or a woman ”will be selected and studied in comparison with the theological views of the Ashariyya Madhhab. Keywords: Imam Maturidi, Kalam, Ahl as-Sunnah, Intellect, Faith